2017
DOI: 10.1182/blood-2017-06-793869
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric antigen receptor T-cell therapies for multiple myeloma

Abstract: Multiple myeloma (MM) is a nearly always incurable malignancy of plasma cells, so new approaches to treatment are needed. T-cell therapies are a promising approach for treating MM, with a mechanism of action different than those of standard MM treatments. Chimeric antigen receptors (CARs) are fusion proteins incorporating antigen-recognition domains and T-cell signaling domains. T cells genetically engineered to express CARs can specifically recognize antigens. Success of CAR-T cells (CAR-Ts) against leukemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
180
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(184 citation statements)
references
References 101 publications
(242 reference statements)
0
180
0
4
Order By: Relevance
“…BCMA is a normal plasma cells marker, falls in to the near-ideal antigen for multiple myeloma with no evidence of expression on the normal non-hematological tissue [144]. Latest multi-center BCMA-CAR trials results indicate a relatively safe profile (although cytokine release syndrome -CRS and transient neurotoxicity were observed) with an overall response rate over 90% [145,146].…”
Section: Beyond Cd19: New Car-t Cells For Solid Tumors -In Search Of mentioning
confidence: 90%
See 1 more Smart Citation
“…BCMA is a normal plasma cells marker, falls in to the near-ideal antigen for multiple myeloma with no evidence of expression on the normal non-hematological tissue [144]. Latest multi-center BCMA-CAR trials results indicate a relatively safe profile (although cytokine release syndrome -CRS and transient neurotoxicity were observed) with an overall response rate over 90% [145,146].…”
Section: Beyond Cd19: New Car-t Cells For Solid Tumors -In Search Of mentioning
confidence: 90%
“…Latest multi-center BCMA-CAR trials results indicate a relatively safe profile (although cytokine release syndrome -CRS and transient neurotoxicity were observed) with an overall response rate over 90% [145,146]. Other antigens currently being targeted to treat hematological malignancies include CD20 for NHL, CD138 for MM [144], CD33 [147], CD123 for AML [148,149] and CD7 for certain leukemias and lymphomas [150]. Lately, using a very elegant approach to treat T-cell malignancies, Pule and colleagues isolated an antibody specific for the TCRβ1 constant region.…”
Section: Beyond Cd19: New Car-t Cells For Solid Tumors -In Search Of mentioning
confidence: 96%
“…While ligation of BCMA promotes myeloma cell proliferation and drug resistance, antibody‐based blockade of BCMA signaling has resulted in some preclinical anti‐MM activity . Thus, BCMA is a rational target for antimyeloma therapy using CAR T cells …”
Section: Introductionmentioning
confidence: 99%
“…20 Thus, BCMA is a rational target for antimyeloma therapy using CAR T cells. 12,21 Several groups have investigated the role of anti-BCMA CAR T-cell therapy in RRMM over recent years. Here, we aim to systematically review the current literature and to summarize results of anti-BCMA CAR T-cell therapies with regard to efficacy and safety in patients with RRMM.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials in multiple myeloma targeting B-cell maturation antigen (BCMA) have proven efficacy and safety of the use of CAR-T in this population [64]. Signaling lymphocyte-activating molecule F7 (SLAMF7), the monoclonal antibody target of elotuzumab, is another promising target in multiple myeloma given its lack of expression outside of hematologic cell line; however, CAR-T targeting this antigen has yet to be used in human clinical trials [65,66]. Many trials of CAR-T in multiple myeloma have shown consistent clinical response but optimization of dose and optimal target antigen still require refinement.…”
Section: Future Directionsmentioning
confidence: 99%